Project of the Goverment of India : - Pekar, F. (Centres of Advanced studies on postgraduate Agriculture Research and Education UNDP - FAO, 1989)
Considering the immense possibilities of gathering raw information on ecological processes through the application of radio-tracer techniques, specific techniques using,...In the background of almost no data collected through the use of radio-isotpoes in Indian freshwater aquaculture research,..